Proxy wars in the Middle East in the 21st century. Τhe role of regional state actors and global powers. The antagonism between Saudi Arabia and Iran, the proxy wars in Syria and Yemen and the interests of global powers – U.S. and Russia – in the regional subsystem of the Middle East. - Νικοπούλου, Αλεξάνδρα (Πανεπιστήμιο Πελοποννήσου, 2023)
The dissertation examines the phenomenon of proxy wars within the context of contemporary civil wars. The phenomenon is studied under the lens of great powers’ retreat from strategic areas of the world, which has allowed regional competitions to flourish. The research focuses on the area of the Middle East after the Arab Spring, where proxy wars have become the norm and have defined regional politics. The study examines the impact of the Iranian-Saudi antagonism on the internal conflicts in Syria and Yemen by adopting a comparative approach to identify the motives of regional actors, and employs proxy wars theory to examine their use as a foreign policy tool. The dissertation also provides valuable insights into the interplay and the power relations between regional and global powers, namely the U.S. and Russia. The essential contribution of this study lies in explaining why and how internal conflicts turn to proxy wars, allowing regional actors to utilize them as foreign policy tools to gain influence and shift the balance of power within a regional sub-system. In doing so, the research provides an innovative understanding of proxy wars in the 21st century, as they acquire a dominant role in the way conflicts take place across the globe and in shaping the new world order.
Πόλεμοι δι’ αντιπροσώπων στη Μέση Ανατολή κατά τον 21ο αιώνα. Ο ρόλος των περιφερειακών κρατών και των μεγάλων δυνάμεων. Ο ανταγωνισμός μεταξύ Σαουδικής Αραβίας και Ιράν, οι πόλεμοι δι’ αντιπροσώπων στη Συρία και την Υεμένη και τα συμφέροντα των μεγάλων δυνάμεων – Η.Π.Α. και Ρωσίας – στο περιφερειακό υποσύστημα της Μέσης Ανατολής.
Keywords: Πόλεμος; Συρία--Ιστορία--Εμφύλιος πόλεμος; Υεμένη--Ιστορία--Εμφύλιος πόλεμος; πόλεμοι δι’ αντιπροσώπων; περιφερειακές δυνάμεις; μεγάλες δυνάμεις; μη κρατικοί δρώντες; Ιράν; Σαουδική Αραβία; Συρία; Υεμένη; Μέση Ανατολή